2016
DOI: 10.1016/j.egja.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of Paracetamol and Dexamethasone with Lidocaine in Intravenous regional anesthesia (IVRA) of upper limbs: A randomized clinical trial

Abstract: Background and aim: Post-operative pain is considered an important complication of Intravenous regional anesthesia (IVRA) which is gaining popularity especially for surgeries on upper limbs. Methods: The present double blind randomized clinical trial was conducted on 60 candidates of upper limb surgeries aged between 20 and 60 years who were of ASA classes 1 or 2. Subjects were randomly assigned to 4 groups: the first group was treated solely with 3 mg/kg of Lidocaine. The second and third groups received the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Reda K. Abdel-Rahman et al, found no statistical significant difference in onset and recovery of sensory block and motor block between lower in lignocaine with paracetamol group than lignocaine only group [15] . Mehrdad Noroozi et al, staed that the mean duration of sensory block was statistically significant among study goups (P<0.001) [16] . Sen H et al, stated that onset duration of motor block was shorter and recovery duration of motor and sensory block was significantly longer in lidocaine and paracetamol group [17] .…”
Section: Discussionmentioning
confidence: 93%
“…Reda K. Abdel-Rahman et al, found no statistical significant difference in onset and recovery of sensory block and motor block between lower in lignocaine with paracetamol group than lignocaine only group [15] . Mehrdad Noroozi et al, staed that the mean duration of sensory block was statistically significant among study goups (P<0.001) [16] . Sen H et al, stated that onset duration of motor block was shorter and recovery duration of motor and sensory block was significantly longer in lidocaine and paracetamol group [17] .…”
Section: Discussionmentioning
confidence: 93%